2006
DOI: 10.1093/humrep/del174
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic studies of Xq critical regions in premature ovarian failure patients

Abstract: Karyotyping is definitely helpful in the evaluation of POF patients. No submicroscopic chromosomal rearrangements affecting Xq region were identified. Further analysis using DNA microarrays should help delineate Xq regions involved in POF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 29 publications
4
45
0
3
Order By: Relevance
“…Lakhal et al detected 34 (5.9%) patients with homogeneous or mosaic X-chromosome aneuploidy out of 568 with secondary amenorrhea. In contrast, Portnoi et al identified no 45,X/46,XX or 46,XX/47,XXX chromosome mosaicisms in any of their POI patients or controls [30].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Lakhal et al detected 34 (5.9%) patients with homogeneous or mosaic X-chromosome aneuploidy out of 568 with secondary amenorrhea. In contrast, Portnoi et al identified no 45,X/46,XX or 46,XX/47,XXX chromosome mosaicisms in any of their POI patients or controls [30].…”
Section: Discussionmentioning
confidence: 87%
“…Also, Eggermann et al presented a familial case of POI women with a small deletion from Xq27.2/Xq27.3 to Xqter [29]. In a population of 90 POI patients, Portnoi et al identified three women bearing a large terminal Xq deletion involving Xq21-qter [30].…”
Section: Chromosome Rearrangementsmentioning
confidence: 99%
“…There was no patient with abnormal secondary sexual characteristics or with characteristic features of Turner syndrome such as short stature, webbed neck, hypoplastic uterus, or other dysmorphic features. The anti-thyroid peroxidase antibody was detected in only a case with 45,X [5] /47,XXX [1] /46,XX [94] . The patient with fragile X premutation carrier was mentally normal but she had a mentally impaired son diagnosed with fragile X syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Premature ovarian insufficiency (POI) is characterized by amenorrhea, the presence of high levels of gonadotropins [folliclestimulating hormone (FSH) > 40 mIU/ml], and low levels of estradiol (E2) for at least 6 months duration in women before the age of 40 [1]. POI occurs in ~1% of the general female population before 40 years of age, as its incidence according to age is approximately 10/100,000 in women aged 15 to 29 years and 79/100,000 in women aged 30 to 39 years [2].…”
Section: Introductionmentioning
confidence: 99%
“…About 9% of POF are related to X chromosome aberrations that comprise both numerical (monosomy and trisomy) and segmental (deletions, isochromosomes and balanced X: autosomal translocations) abnormalities [26][27][28]. The complete or partial absence of one X chromosome is associated with Turner syndrome characterized by defective ovarian function and gonadal dysgenesis [29].…”
Section: Chromosome X Defects In Pofmentioning
confidence: 99%